Konsep Ihsan Perspektif Tasawuf - Ali Hamidi (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2017)
Islam is built on three main runway, which is Iman, Islam and Ihsan. Therefore, a Muslim should not regard ihsan it is only the main character, but rather should be seen as part of the creed and the largest part of his Islam. Ihsan aspect is seen as a quest for perfection in understanding the activities of the Islamic religion. Fundamentally, these three aspects should not be understood partially. Ihsan applicative can be understood from a scientific discipline that is Sufism. Wealth understanding of Sufism is able to answer what it takes to achieve ihsan. Sufism start everything from the inside, feeling or intuition becomes the central point of the start of the flow of understanding of Sufism. And for that reason aspect of charity in the teachings of Islam were able to accomplish. This paper attempts to explain briefly about the charity aspect and Sufism in Islam. Principal discussion is to explain the meaning of ihsan, the position of ihsan, explanation of Sufism as well as how the charity aspect in relation to Sufism.